SURGICAL AUDIT - LAPAROSCOPIC CHOLECYSTECTOMY IN A FREE CAMP AT PRIVATE SECTOR HOSPITAL - Abdul Ghani Soomro; Tufail Ahmed Baloch; Moin-ul-Islam; Mairaj Muhammad (Journal of University Medical & Dental College, 2020)
BACKGROUND & OBJECTIVE: Laparoscopic Cholecystectomy is usual method for the treatment of gall bladder stone disease and is practiced all over the world due to many beneﬁts like fasten the recovery time. Furthermore, it reduced the post-operative pain and period of hospital stay. To conduct Surgical Audit and evaluate safety of Laparoscopic cholecystectomy.METHODOLGY: This prospective study was conducted in a private hospital at Hyderabad during free camps of Laparoscopic Cholecystectomy. Four camps were arranged in 2016 - 2019. Total number of 190 patients  underwent Laparoscopic Cholecystectomy during the study period. The patient's age falls between 12–65 years. A detailed history, relevant investigation and Cardiac ﬁtness were evaluated. All patients underwent four ports Lap-Chole. Data was collected assessed and audit was performed and safety was evaluated.RESULTS: Total 190 patients operated females 88.45% and males 11.55%. 115 (60.50%)were in  the range of 30-35 years followed by 55 (28.95%)patients in the range of 40-50 years.8 (4.20%) patients were converted to open cholecystectomy, 4 due to bleeding from liver bed, 3 patients due to diﬃcult dissection in calots triangle and 1 due to Empyema of gall bladder.10 patients (5.50%) had Trocar site bleeding, 10 patients (5.50%) had gall bladder injury, in 4 cases had spillage of stones and 72 patients (38.50%) developed umbilical port site infection 1 patient develop port site hernia. No mortality was recorded in this study.CONCLUSION: Our Surgical Audit proves that Laparoscopic Cholecystectomy is a safe procedure on the basis of only 4.2% intra operative and 5.5% postoperative complications and gaining wide spread popularity among our population due to less pain, less hospital stay. We recommend other private hospitals to extent such services to our poor population with symptomatic cholelithiasis.